Are lifting straps a game changer for resistance training or an overrated tool? An exploratory review of current evidence and future research directions - Martins, R.; Rosa, M.; Padovan, R.; Sá, M.; Antunes, J. P.; Afonso, J.; García-Ramos, A. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Lifting straps (LS) are popular tools used by resistance-training (RT) practitioners with the intention of improving exercise performance. This tool is worn around the wrist to enhance grip on the barbell or other RT equipment and potentially decrease grip limitation throughout the exercise—a limitation that is usually reported by practitioners, especially during deadlifts, weightlifting movements, and pulling exercises. However, this knowledge remains mostly based on common experiential beliefs. Thus, this narrative review aims to highlight the current knowledge on the impact of LS in RT, focusing on physiological and biomechanical effects, exercise performance, chronic training adaptations, and safety concerns, and also to expose the existing literature gaps and distinguish between evidence-based findings and empirical assumptions. Conclusion: Evidence suggests that LS can enhance maximal strength and grip perception. However, for pulling/back exercises, no consistent effects have been observed. In addition, LS may increase mechanical work in the deadlift, but contrary to common belief, they appear not to contribute to increased muscle recruitment. Furthermore, no scientific evidence supports the chronic effects of LS usage in training; it is still a hypothesis. Finally, this review offers future research insights to assist sport scientists in designing and conducting more comprehensive investigations on this topic, ultimately enhancing the understanding and application of LS in RT.